A Study on Evaluating Tourists’ Destination Accommodation Experiences (International Journal of Environmental Sciences, 2025)
Today, tourists' destination selection processes are directly shaped by the comments and evaluations shared on digital platforms. Especially potential tourists who are searching for information before their travel get a preliminary impression of the destinations they plan to go through these platforms. This situation increases the importance of online user comments in terms of the promotion of touristic destinations and destination marketing. Sinop is one of the important touristic destinations known for its nature and historical texture, located in the north of the Black Sea Region. This study aims to evaluate the opinions of visitors who visited the Sinop destination and received service from public and private accommodation enterprises regarding their accommodation experiences by examining the Google comments. By examining the comments made on the Google platform, it will be possible to understand in depth the perceptions, expectations and experiences of tourists towards accommodation enterprises. In this way, the strengths and weaknesses of both the accommodation enterprises and the destination they are a component of are determined, and information that can contribute to Sinop destination tourism strategies is presented. In this context, comments regarding accommodation enterprises were evaluated using the content analysis method. Within the scope of the research, positive visitor comments regarding public accommodation enterprises include the concepts of price, proximity to the sea, silence, comfort and ideal holiday destination; in negative visitor comments about public accommodation establishments, the concepts of management indifference, old room equipment, expensive restaurants, no standard breakfast service and low product variety came to the fore. In positive visitor comments about private accommodation establishments, the concepts of magnificent atmosphere, hospitality, quality service, clean rooms and comfort came to the fore; in negative visitor comments about private accommodation establishments, the concepts of expensive prices, reservation problems, poorly equipped rooms, parking problems and old room equipment came to the fore.